2019
DOI: 10.1039/c9sc03161h
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen self-sufficient NIR-activatable liposomes for tumor hypoxia regulation and photodynamic therapy

Abstract: We have presented oxygen self-sufficient near infrared-activatable liposomes to overcome hypoxia-associated photodynamic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 45 publications
0
56
0
Order By: Relevance
“…Indeed, a careful review of the literature reveals that very few systemsthat are believed to be active under hypoxiahave actually been tested against cells under low oxygen conditions. 41,[48][49][50][51][52][53][54] Likewise, relatively few systems have been tested for photodissociation in cell-free conditions under low oxygen conditions (i.e., 0-3%). 37,49,50,52,55 Performing experiments under hypoxic conditions is challenging due to a variety of factors such as the initial establishment of low oxygen tension or differences in cellular growth and metabolismif the cells can even grow at the desired oxygen level.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a careful review of the literature reveals that very few systemsthat are believed to be active under hypoxiahave actually been tested against cells under low oxygen conditions. 41,[48][49][50][51][52][53][54] Likewise, relatively few systems have been tested for photodissociation in cell-free conditions under low oxygen conditions (i.e., 0-3%). 37,49,50,52,55 Performing experiments under hypoxic conditions is challenging due to a variety of factors such as the initial establishment of low oxygen tension or differences in cellular growth and metabolismif the cells can even grow at the desired oxygen level.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia is a characteristic hallmark of the microenvironment in solid tumors, resulting on one side from upregulated metabolism, especially in fast-growing aggressive tumors, and on the other side, from insufficient oxygenation through aberrant blood vessels [ 7 , 8 , 9 ]. Moreover, the conversion of O 2 to ROS throughout PDT and SDT rapidly depletes available oxygen, which constrains the treatment duration [ 6 , 10 ]. It has to be emphasized that hypoxia not only strongly correlates with the aggressiveness of cancer, but also promotes tumor metastasis and tumor resistance to chemotherapy, radiotherapy, and immunotherapy [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] Design of the next generation of PSs has been focused on extending the absorption window to include NIR wavelengths (700-900 nm) [31][32][33][34] and to alter the excited state properties of the molecules to exploit oxygen-independent mechanistic pathways to achieve phototoxic effects in hypoxia. [35][36][37][38][39][40] Ru II polypyridyl complexes are particularly attractive scaffolds for PS design because the photophysics of these complexes is wellestablished [41][42][43][44][45][46][47] and polypyridyl ligand combinations can be chosen to systematically manipulate the excited state dynamics in a rational and consistent manner. Following this strategy, our group developed the photosensitizer TLD1433 [47][48][49] and demonstrated that extremely efficient singlet oxygen sensitization can be obtained with both Ru II and Os II complexes containing oligothienyl-based ligands with low-energy triplet intraligand charge transfer ( 3 ILCT) excited states that are characterized by microsecond lifetimes.…”
Section: Introductionmentioning
confidence: 99%